SaaS : A Commerce Manoeuvre on the Indian Economy - Yadav, Kavita (Indian Journal of Computer Science, 2025)
A much talked about software, apparently revolutionary in nature, in computing Commerce and trade analytics for future commercial and economic projects, has primarily been SaaS (Software as a Service). In the process of digitizing economic affairs, AI-enabled support with numerous machine tools has been underway in the Indian economy with robust deliveries and holistic developments. The current study undertakes the details of scientific tools and methods while paving the way for SaaS in competitive economies. The operational efficiency of optimizing manufacturing, production, and distribution deliveries of goods and services for consumption, investments & savings, the precision role, implementation, and contribution of SaaS shall be seemingly overwhelming in the future course of commercial and economic actions. The coherent assessment shall be organized through programs by content analysis. Information from software and social media will be analyzed in the upcoming study to arrive at the findings and conclusion of the study.